New Improved ACO Algorithm for Selective Harmonic Elimination in Multilevel Inverter - et. al., Sarika D Patil, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents new improved proposed algorithm over the basic Ant colony optimization algorithm to enhance the convergence speed, global ability for solution and to avoid from stucking into local optima. This (NEWACO) algorithm mainly aims at adaptive adjustment control of pheromone with active evaporation factor for updation. The movement and pheromone deposition is improved and making it flexible for solving large scale problems. Hence this proposed (NEWACO) algorithm is applied for solving selective harmonic elimination equations which are nonlinear transcendental equation thereby providing optimized solution for switching angles and minimizing Total Harmonic Distortion (THD). The various simulated and experimental results show that this new proposed algorithm can be used for finding the global minima with high convergence performance. It proves its effectiveness over the other conventional methods too.